Myocardial Hemorrhage After Acute Reperfused ST-Segment–Elevation Myocardial Infarction: Relation to Microvascular Obstruction and Prognostic Significance. (January 2016) - Carrick, David; Haig, Caroline; Ahmed, Nadeem; McEntegart, Margaret; Petrie, Mark C.; Eteiba, Hany; Hood, Stuart; Watkins, Stuart; Lindsay, M. Mitchell; Davie, Andrew; Mahrous, Ahmed; Mordi, Ify; et al.
Abstract : Background—: The success of coronary reperfusion therapy in ST-segment–elevation myocardial infarction (MI) is commonly limited by failure to restore microvascular perfusion. Methods and Results—: We performed a prospective cohort study in patients with reperfused ST-segment–elevation MI who underwent cardiac magnetic resonance 2 days (n=286) and 6 months (n=228) post MI. A serial imaging time-course study was also performed (n=30 participants; 4 cardiac magnetic resonance scans): 4 to 12 hours, 2 days, 10 days, and 7 months post reperfusion. Myocardial hemorrhage was taken to represent a hypointense infarct core with a T2* value of <20 ms. Microvascular obstruction was assessed with late gadolinium enhancement. Adverse remodeling was defined as an increase in left ventricular end-diastolic volume ≥20% at 6 months. Cardiovascular death or heart failure events post discharge were assessed during follow-up. Two hundred forty-five patients had evaluable T2* data (mean±age, 58 [11] years; 76% men). Myocardial hemorrhage 2 days post MI was associated with clinical characteristics indicative of MI severity and inflammation. Myocardial hemorrhage was a multivariable associate of adverse remodeling (odds ratio [95% confidence interval]: 2.64 [1.07–6.49]; P =0.035). Ten (4%) patients had a cardiovascular cause of death or experienced a heart failure event post discharge, and myocardial hemorrhage, but not microvascular obstruction, was associated with this composite adverse outcome (hazard ratio, 5.89; 95% confidence interval, 1.25–27.74; P =0.025), including after adjustment for baseline left ventricular end-diastolic volume. In the serial imaging time-course study, myocardial hemorrhage occurred in 7 (23%), 13 (43%), 11 (33%), and 4 (13%) patients 4 to 12 hours, 2 days, 10 days, and 7 months post reperfusion. The amount of hemorrhage (median [interquartile range], 7.0 [4.9–7.5]; % left ventricular mass) peaked on day 2 ( P <0.001), whereas microvascular obstruction decreased with time post reperfusion. Conclusions—: Myocardial hemorrhage and microvascular obstruction follow distinct time courses post ST-segment–elevation MI. Myocardial hemorrhage was more closely associated with adverse outcomes than microvascular obstruction. Clinical Trial Registration—: URL:http://www.clinicaltrials.gov . Unique identifier: NCT02072850. Abstract : Supplemental Digital Content is available in the text.